The ParentingWell Practice Approach: Facilitating implementation in U.S. adult mental health services - Heyman, Miriam; Nicholson, Joanne; English, Kelly (Frontiers in Psychiatry, 2024)
Background: To address the need for interventions for families with parents with mental illness, the evidence-based intervention Let's Talk about Children (LTC) was adapted in the context of adult mental health services in the United States and reframed as the ParentingWell Practice Approach. This study focuses on the early implementation phase of the adapted practice in Massachusetts. Methods: As part of the adaptation and implementation process, practitioners from provider agencies serving adults with mental illness were invited to participate in the ParentingWell Learning Collaborative (PWLC), which included in-person learning collaborative sessions and follow-up virtual coaching sessions. This paper focuses on data obtained during and in response to the PWLC virtual coaching sessions, from 29 participants. Specific research questions included: (1) What themes emerged in coaching sessions related to practitioners' experiences during the early implementation of the ParentingWell practice approach? (2) In what ways are coaching sessions helpful to the practitioners as they implement the ParentingWell practice approach? Coaching sessions were recorded, and transcribed, and the data were analyzed qualitatively to identify early implementation themes. Practitioners completed feedback surveys online (which included Likert scale items and open-ended questions) following virtual coaching sessions to evaluate the usefulness of coaching sessions. Results: Coaching sessions reflected the following themes related to practitioners' experiences during the early implementation of ParentingWell: (1) practitioners identify and share concrete approaches to supporting parents; (2) practitioners reflect on parents' needs related to support, advocacy, problem-solving, and parenting skills; (3) practitioners reflect on their own personal experiences; and (4) practitioners' recognize the importance of self-care strategies for themselves and for parents served. Practitioners indicated that coaching sessions were useful in supporting the implementation of a new practice. Conclusion: This study provides preliminary evidence for the benefits of coaching in the implementation of ParentingWell. Future research will explore the impact of ParentingWell on outcomes for parents and families served.